Nonspherical dynamics and microstreaming of a wall-attached microbubble. (25th March 2022) - Fauconnier, M.; Mauger, C.; Béra, J.-C.; Inserra, C.
Abstract: Abstract : Acoustic microstreaming is a nonlinear response of a fluid that undergoes high-amplitude acoustic stimulation and tends to viscously absorb it. The present experimental study investigates the generation of acoustic microstreaming induced by an oscillating wall-attached bubble undergoing nonspherical shape modes. From a microscope top view, the formation of particular flow signatures is explored for the main classes of spherical harmonics Y_nm(θ, φ ) : zonal ( m = 0 < n ), sectoral ( n = m > 0 ) and tesseral ( 0 < m < n ) oscillation. The microstreaming induced by a bubble animated by a sectoral mode alone reveals a pattern characterized by a 4n -lobe flower shape. Tesseral modes give rise to 4 m -lobe flower-shaped patterns. Finally, when sectoral and zonal modes coexist, two kinds of pattern stand out: 2n -lobe flower shape and n -pointed star shape. The preferential emergence of one or another streaming pattern is discussed on the basis of the amplitude and phase shift between both shape modes.